Genetic analysis of agronomical traits in recombinant inbred lines of cowpea (Vignaunguiculata(L.) Walp.)under two water regimes. - TONESSIA, Charlotte; KOUASSI, N'Dri; CISSE, Ndiaga; Aké, Severin (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Single nucleotide polymorphism (SNP) markers were used to develop a genetic-linkage map and to identify QTLsinvolved in the genetic variation of agronomical traits in cowpeaunder two water regimes. A total of 1536 SNP GoldenGate assay were used to screen for polymorphism in a cowpea population of recombinant inbred lines. A total of 299 SNP markers amplified polymorphic products of which 228 mapped to the 11 cowpea linkage groups with an average distance of 6.5 cM between markers. The new SNP genetic map with a total length of 1281,8 cM were aligned with the consensus cowpea map allowing filling some gaps, which will increase QTLs analysis. A total of 31 QTLs affecting agronomic traits were identified and mapped to cowpea genomic regions. Among them 45% explaining from 3 to 35% of genetic variation were detected for both water conditions. Co-locations between QTLs were identified on several linkage groups among them QTLs affecting harvest index (HI) and grain yield suggesting their common genetic bases. Because, HI has been shown as the most stable and highly correlated parameter with cowpea yield under stress; our results will enable the efficiency of MAS and enhance genetic progress in cowpea.